Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
To find the equation of the tangent line to the curve given by [tex]\(x^6 y^6 = 64\)[/tex] at the point [tex]\((2, 1)\)[/tex], we will use implicit differentiation and then apply the point-slope form of the line equation. Here is the step-by-step process:
1. Given Equation:
[tex]\[ x^6 y^6 = 64 \][/tex]
2. Implicit Differentiation:
To find the derivative [tex]\(\frac{dy}{dx}\)[/tex], we differentiate both sides of the equation with respect to [tex]\(x\)[/tex], treating [tex]\(y\)[/tex] as a function of [tex]\(x\)[/tex] (i.e., [tex]\(y = y(x)\)[/tex]).
[tex]\[ \frac{d}{dx}(x^6 y^6) = \frac{d}{dx}(64) \][/tex]
The right side is:
[tex]\[ \frac{d}{dx}(64) = 0 \][/tex]
Now, for the left side, we use the product rule:
[tex]\[ \frac{d}{dx}(x^6 y^6) = x^6 \frac{d}{dx}(y^6) + y^6 \frac{d}{dx}(x^6) \][/tex]
Using the chain rule for [tex]\(y^6\)[/tex]:
[tex]\[ \frac{d}{dx}(y^6) = 6y^5 \frac{dy}{dx} \][/tex]
And straightforward differentiation for [tex]\(x^6\)[/tex]:
[tex]\[ \frac{d}{dx}(x^6) = 6x^5 \][/tex]
So our equation becomes:
[tex]\[ x^6 \cdot 6y^5 \frac{dy}{dx} + y^6 \cdot 6x^5 = 0 \][/tex]
3. Solve for [tex]\(\frac{dy}{dx}\)[/tex]:
[tex]\[ 6x^6 y^5 \frac{dy}{dx} + 6x^5 y^6 = 0 \][/tex]
Factor out the common terms:
[tex]\[ 6x^5 y^5 (x \frac{dy}{dx} + y) = 0 \][/tex]
Simplify and solve for [tex]\(\frac{dy}{dx}\)[/tex]:
[tex]\[ x \frac{dy}{dx} + y = 0 \][/tex]
[tex]\[ \frac{dy}{dx} = -\frac{y}{x} \][/tex]
4. Evaluate at the Point (2, 1):
We now find the slope of the tangent line at the point [tex]\((2, 1)\)[/tex]:
[tex]\[ \left. \frac{dy}{dx} \right|_{(2, 1)} = -\frac{y}{x} = -\frac{1}{2} \][/tex]
5. Equation of the Tangent Line:
The point-slope form of the line equation is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Here, [tex]\((x_1, y_1) = (2, 1)\)[/tex] and the slope [tex]\(m = -\frac{1}{2}\)[/tex]:
[tex]\[ y - 1 = -\frac{1}{2}(x - 2) \][/tex]
So, the equation of the tangent line to the curve [tex]\(x^6 y^6 = 64\)[/tex] at the point [tex]\((2, 1)\)[/tex] is:
[tex]\[ y - 1 = -\frac{1}{2}(x - 2) \][/tex]
Or simplifying:
[tex]\[ y - 1 = -\frac{1}{2}x + 1 \][/tex]
[tex]\[ y = -\frac{1}{2}x + 2 \][/tex]
Therefore, the equation of the tangent line at the point [tex]\((2, 1)\)[/tex] is:
[tex]\[ y = -\frac{1}{2}x + 2 \][/tex]
1. Given Equation:
[tex]\[ x^6 y^6 = 64 \][/tex]
2. Implicit Differentiation:
To find the derivative [tex]\(\frac{dy}{dx}\)[/tex], we differentiate both sides of the equation with respect to [tex]\(x\)[/tex], treating [tex]\(y\)[/tex] as a function of [tex]\(x\)[/tex] (i.e., [tex]\(y = y(x)\)[/tex]).
[tex]\[ \frac{d}{dx}(x^6 y^6) = \frac{d}{dx}(64) \][/tex]
The right side is:
[tex]\[ \frac{d}{dx}(64) = 0 \][/tex]
Now, for the left side, we use the product rule:
[tex]\[ \frac{d}{dx}(x^6 y^6) = x^6 \frac{d}{dx}(y^6) + y^6 \frac{d}{dx}(x^6) \][/tex]
Using the chain rule for [tex]\(y^6\)[/tex]:
[tex]\[ \frac{d}{dx}(y^6) = 6y^5 \frac{dy}{dx} \][/tex]
And straightforward differentiation for [tex]\(x^6\)[/tex]:
[tex]\[ \frac{d}{dx}(x^6) = 6x^5 \][/tex]
So our equation becomes:
[tex]\[ x^6 \cdot 6y^5 \frac{dy}{dx} + y^6 \cdot 6x^5 = 0 \][/tex]
3. Solve for [tex]\(\frac{dy}{dx}\)[/tex]:
[tex]\[ 6x^6 y^5 \frac{dy}{dx} + 6x^5 y^6 = 0 \][/tex]
Factor out the common terms:
[tex]\[ 6x^5 y^5 (x \frac{dy}{dx} + y) = 0 \][/tex]
Simplify and solve for [tex]\(\frac{dy}{dx}\)[/tex]:
[tex]\[ x \frac{dy}{dx} + y = 0 \][/tex]
[tex]\[ \frac{dy}{dx} = -\frac{y}{x} \][/tex]
4. Evaluate at the Point (2, 1):
We now find the slope of the tangent line at the point [tex]\((2, 1)\)[/tex]:
[tex]\[ \left. \frac{dy}{dx} \right|_{(2, 1)} = -\frac{y}{x} = -\frac{1}{2} \][/tex]
5. Equation of the Tangent Line:
The point-slope form of the line equation is:
[tex]\[ y - y_1 = m(x - x_1) \][/tex]
Here, [tex]\((x_1, y_1) = (2, 1)\)[/tex] and the slope [tex]\(m = -\frac{1}{2}\)[/tex]:
[tex]\[ y - 1 = -\frac{1}{2}(x - 2) \][/tex]
So, the equation of the tangent line to the curve [tex]\(x^6 y^6 = 64\)[/tex] at the point [tex]\((2, 1)\)[/tex] is:
[tex]\[ y - 1 = -\frac{1}{2}(x - 2) \][/tex]
Or simplifying:
[tex]\[ y - 1 = -\frac{1}{2}x + 1 \][/tex]
[tex]\[ y = -\frac{1}{2}x + 2 \][/tex]
Therefore, the equation of the tangent line at the point [tex]\((2, 1)\)[/tex] is:
[tex]\[ y = -\frac{1}{2}x + 2 \][/tex]
Thank you for choosing our service. We're dedicated to providing the best answers for all your questions. Visit us again. We hope our answers were useful. Return anytime for more information and answers to any other questions you have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.